Analisis School Belonging Peserta Didik SMP Negeri 4 Sungai Raya Kabupaten Kubu Raya - Zamzam, Intan; Ulfa, Maria; Karolina, Venny; Ramadhan, Iwan; Fitriana, Dina (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to analyze the level of school belonging of class VIII students at SMP Negeri 4 Sungai Raya, Kubu Raya Regency. School belonging plays an important role in increasing students' learning motivation and psychological well-being. This research uses a descriptive quantitative method with a questionnaire as a data collection instrument. The research results show that the majority of class VIII students at SMP Negeri 4 Sungai Raya, Kubu Raya Regency, have a moderate to high level of school belonging, supported by positive social ties with peers and teachers. However, there are a small number of class VIII students at SMP Negeri 4 Sungai Raya, Kubu Raya Regency, students with low engagement who feel less welcome in the school environment. Therefore, creating an inclusive and supportive school environment is very important to increase students' attachment to school.